Industrial Change in China : Economic Restructuring and Conflicting Interests. - Hannan, Kate (Routledge studies--China in transition, 1998)
This book analyses the industrial reform measures taken by the Chinese government during the decade 1985-95 and the economic and political tensions between state enterprise reform and an authoritative political leadership.